Green Energy Development Strategy Towards Green Logistics: Case Study At PT. Pelabuhan Indonesia III (Persero) Benoa Bali - Dwipayana, Arif Devi; Darmayanti, Ni Luh (Jurnal Manajemen Industri dan Logistik, 2024)
Implementing green logistics involves using environmentally friendly practices and technologies in the management of supply chains and transportation of goods. The potential benefits gained in implementing green logistics include, a reduction in greenhouse gas emissions, energy, and resource efficiency, reduced operational costs, reputation, and regulatory compliance. This research aims to create a strategy for developing the use of green energy towards green logistics at Benoa Port. The research methodology using a systematic literature review hybrid type then present several development strategy schemes that will be implemented. The results of the research conclude that the sea side and land side strategies can be applied to Benoa Port, the initial development strategy that has the greatest potential to be implemented is wind energy and solar energy on the land side to support the implementation of green logistics in fulfilling the Port area's electrical energy, the implications of this research will have an impact on the development of green energy for other ports in Indonesia in accordance with the government's national energy policy.